2014
DOI: 10.1007/s13539-014-0133-2
|View full text |Cite
|
Sign up to set email alerts
|

1‐Sarcosine–angiotensin II infusion effects on food intake, weight loss, energy expenditure, and skeletal muscle UCP3 gene expression in a rat model

Abstract: BackgroundThere are a myriad of proteins responsible for modulation of expenditure of energy. Angiotensin II (Ang II) is a vital component of renin-angiotensin system that affects blood pressure and also linked to both cachexia and obesity via fat and muscle metabolism. Previous research suggests that the direct action of Ang II is on the brain, via angiotensin II type 1 receptor protein, affecting food intake and energy expenditure. The objective of the study is to investigate the effect of 1-sarcosine (SAR)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…In addition, cerebral ventricular AngII infusion (50 ng/kg per min) reduces food intake, which is completely prevented by candesartan [3]. In Sprague-Dawley rats, AngII infusion impairs appetite and decreases body weight by inducing wasting predominantly in adipose tissue [15]. These findings are in accordance with the evidence showing that AT1R knockout mice are hyperphagic [16], and suggest that RAS system is directly involved in appetite regulation.…”
Section: Renin Angiotensin System Anorexia and Body Weightsupporting
confidence: 84%
“…In addition, cerebral ventricular AngII infusion (50 ng/kg per min) reduces food intake, which is completely prevented by candesartan [3]. In Sprague-Dawley rats, AngII infusion impairs appetite and decreases body weight by inducing wasting predominantly in adipose tissue [15]. These findings are in accordance with the evidence showing that AT1R knockout mice are hyperphagic [16], and suggest that RAS system is directly involved in appetite regulation.…”
Section: Renin Angiotensin System Anorexia and Body Weightsupporting
confidence: 84%
“…It has been reported that systemic infusion of AngII or AngII analog increases energy expenditure and reduces WAT mass in rodents. 66 , 67 However, AngII infusion is usually associated with many systemic adverse effects produced by AT1R (for example, hypertension). 66 Therefore, direct activation of AT2R by introducing exogenous selective agonists and making endogenous AngII-induced basal AT2R activity more prominent by inhibiting AT1R should be better strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II ‐induced body wasting is due to both anorexigenic and catabolic effects . Recently, Cichello et al . showed a direct effect of Ang II infusion on appetite impairment and body weight loss mostly due to adipose tissue wasting.…”
Section: Emerging Biomarkers Of Cardiac Cachexiamentioning
confidence: 99%
“…16 Ang II-induced body wasting is due to both anorexigenic and catabolic effects. 72,73 Recently, Cichello et al 74 showed a direct effect of Ang II infusion on appetite impairment and body weight loss mostly due to adipose tissue wasting. Sanders et al 75 have reported a direct catabolic effect on skeletal muscle by Ang II with increased intracellular protein degradation in murine myotubes through an increased expression of the UPP.…”
Section: Metabolic Biomarkersmentioning
confidence: 99%